CONSTRUCTING AN INDEX FOR CROSS-BORDER ECOMMERCE DEVELOPMENT LEVELS BASED ON ECOSYSTEM THEORY : EMPIRICAL INSIGHTS FROM RCEP COUNTRIES - Li, Li Zhang; Muhammad Asraf, Abdullah; Min, Huang; Li, Hong Dai (UNIMAS Publisher, 2025)
This study assesses the development levels of cross-border e-commerce among Regional Comprehensive Economic Partnership (RCEP) nations from 2013 to 2022. The study synthesizes global literature on ecommerce ecosystem theories, key influencing factors, and measurement approaches to construct a multidimensional indicator system. This system integrates the TIMG index to provide a comprehensive analysis of the digital economy's impacts. By employing principal component analysis in Stata, the study formulates a scoring methodology to evaluate e-commerce development across RCEP nations, highlighting trends over the decade. The results identify China, Japan, and Singapore as leading nations, followed closely New Zealand, Malaysia, Thailand, Indonesia, Vietnam, and the Philippines comprise the third tier, while Laos ranks at the lowest development level. The study emphasizes the critical roles of logistics and information flow in e-commerce development, providing valuable insights for future explorations within the RCEP framework.